Analisis Analisis Penerapan Parenting The Hartono's Family dalam Mengembangkan Emosional Anak - Fitriani, Faizatul (Jurnal Tarbiyah dan Ilmu Keguruan Borneo, 2024)
Increasing children's emotional intelligence really requires a role model who is able to enable children to understand their own emotions. One of the roles needed is parents and how to introduce children's emotions in effective and positive ways. The Hartono's Family is one of the families that applies parenting well in developing children's emotional intelligence. This research uses a content analysis method with a descriptive approach. Researcher examined the videos that were distributed, then presented information contained in them in the form of narrative-description. The aim of this research is to find out and describe the parenting patterns implemented by The Hartono's Family. The results show that implementing parenting with a democratic parenting model really helps the development of emotional intelligence in young children. Keywords: The Hartono’s Family, Emotional Intelegence, Young Children.